Adaptation: This Won't Hurt a Bit! - Balan, Rajesh Krishna; Sousa, Joao Pedro; Okoshi, Tadashi; Flinn, Jason; Narayanan, Dushyanth; Matsutsuka, Takahide; Satyanarayanan, Mahadev (Proceedings of the 4th IEEE Workshop on Mobile Computing Systems and Applicatons (WMCSA 2002), 2002)
With the prevalance of handheld devices, it is increasingly necessary to build systems that adapt applications according to the available resources. These systems offer new and constantly changing interfaces for adaptation. Integrating applications with these systems requires extensive modiﬁcation and maintainence: this is painful! In this paper, we present an approach that allows application writers to easily integrate their applications with an adaptive runtime system. This approach involves the use of a high level description language coupled with a runtime-speciﬁc stub generator. We present two case studies of enhancing applications for adaptation using our approach. Our case studies show that our approach is viable and can help to ease the integrationof applications into adaptive runtime systems.